#### Answer

$9$

#### Work Step by Step

RECALL:
(i) $(a+b)(a-b) = a^2-b^2$
(ii) $\sqrt{a}^2=a, a \ge0$
Use rule (i) above to obtain:
$=4^2-\sqrt{7}^2
\\=16-\sqrt{7}^2$
Use rule (ii) above to obtain:
$=16-7
\\=9$

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

$9$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.